Atitudes e vulnerabilidades frente ao aborto provocado em contextos de legalidade e ilegalidade - Wiese, Íria Raquel Borges (2017)
This study aimed at investigating the values, gender beliefs, attitudes and vulnerabilities associated to induced abortion in a context of illegality (Brazil - Paraíba) and legality (Uruguay - Montevideo). This thesis is that attitudes towards induced abortion can be explained by the psychosocial values and gender beliefs of a society. Such attitudes, contrary or favorable, demarcate contexts of illegality and legality, respectively, which reduce, reproduce or increase situations of vulnerability experienced by women who practice abortion, and can influence their experience and meanings. In order to answer the thesis and general objective presented, three studies were carried out. Study 1 consisted of the translation, adaptation and validation of the Gender Attitude Inventory (GAI) and Psychosocial Values Questionnaires (QVP-24) used in study 2. This, in turn, also of a quantitative nature, aimed at analyzing a predictive model of the attitudes of university students, in both contexts, against ou favorable to the the right to induce abortion, having as explanatory variables the psychosocial values and the gender beliefs. Finally, study 3 (qualitative) aimed at identifying and analyzing the elements that reduce, reproduce or increase certain vulnerabilities involved in induced abortion from the discourse of the women who practiced it. At the same time, it was intended to investigate how such contexts (of legality and illegality) reflect in the experience and meanings produced by women who induced abortion. In order to identify the values, gender beliefs, attitudes and vulnerabilities associated with induced abortion, it is intended to elucidate elements that may provide subsidies for health promotion. The participantes os the study 1 and 2, were 398 Brazilian university students, as well as 384 Uruguayan students. After the validation of these measurement instruments, the study 2 was carried out. In the analysis of the predictive model of attitudes towards induced abortion, differences between the two legislative contexts were observed. In the context of illegality (Brazil - Paraíba), the variables that explained these attitudes were: the religious system (23%), modern beliefs about sexual initiative by both men and women (8% ), the hedonistic value system (3%) and the modern (constructivist) beliefs regarding differences in family and sexual roles (1%). In the context of legality (Uruguay - Montevideo), four variables explained attitudes towards induced abortion: female sexual freedom (18%), religiosity (7%), difference in professional roles (4%) and difference in family and sexual roles (2%). Finally, 17 Uruguayan women and 13 Brazilian women who had abortions participated in the study 3, who responded to a semi-structured interview, using a methodology based on the scene method, which considers the subjectivity of people and their socio-cultural context. The data were analyzed based on thematic categorization. For both contexts, four categories emerged, which refer to the scenes of interest in this study, namely: the moment of sexual intercourse that generated unplanned and unwanted gestation, represented by the category named "Affective-sexual relationship and Sexual and reproductive rights"," Discovering pregnancy and trajectory "," Decision on abortion and trajectory "and, finally," Post-abortion experience ". It was observed, in general, that social subjectivity, historically configured in social and at the same time in individual scenarios, resounded on the vulnerabilities, experience and meanings of the women who induced abortion in the context of legality and illegality.